Gastroschisis: one year outcomes from national cohort study. (15th November 2011) - Bradnock, Timothy J; Marven, Sean; Owen, Anthony; Johnson, Paul; Kurinczuk, Jennifer J; Spark, Patsy; Draper, Elizabeth S; Knight, Marian
Abstract : Objective To describe one year outcomes for a national cohort of infants with gastroschisis. Design Population based cohort study of all liveborn infants with gastroschisis born in the United Kingdom and Ireland from October 2006 to March 2008. Setting All 28 paediatric surgical centres in the UK and Ireland. Participants 301 infants (77%) from an original cohort of 393. Main outcome measures Duration of parenteral nutrition and stay in hospital; time to establish full enteral feeding; rates of intestinal failure, liver disease associated with intestinal failure, unplanned reoperation; case fatality. Results Compared with infants with simple gastroschisis (intact, uncompromised, continuous bowel), those with complex gastroschisis (bowel perforation, necrosis, or atresia) took longer to reach full enteral feeding (median difference 21 days, 95% confidence interval 9 to 39 days); required a longer duration of parenteral nutrition (median difference 25 days, 9 to 46 days) and a longer stay in hospital (median difference 57 days, 29 to 95 days); were more likely to develop intestinal failure (81% (25 infants) v 41% (102); relative risk 1.96, 1.56 to 2.46) and liver disease associated with intestinal failure (23% (7) v 4% (11); 5.13, 2.15 to 12.3); and were more likely to require unplanned reoperation (42% (13) v 10% (24); 4.39, 2.50 to 7.70). Compared with infants managed with primary fascial closure, those managed with preformed silos took longer to reach full enteral feeding (median difference 5 days, 1 to 9) and had an increased risk of intestinal failure (52% (50) v 32% (38); 1.61, 1.17 to 2.24). Event rates for the other outcomes were low, and there were no other significant differences between these management groups. Twelve infants died (4%). Conclusions This nationally representative study provides a benchmark against which individual centres can measure outcome and performance. Stratifying neonates with gastroschisis into simple and complex groups reliably predicts outcome at one year. There is sufficient clinical equipoise concerning the initial management strategy to embark on a multicentre randomised controlled trial comparing primary fascial closure with preformed silos in infants suitable at presentation for either treatment to determine the optimal initial management strategy and define algorithms of care.